PENGARUH MODAL, LAMA USAHA, JAM KERJA, DAN PENDIDIKAN PADA PENDAPATAN PEDAGANG DI SEKITAR KAWASAN WISATA PESANGGRAHAN DANAU SINGKARAK KABUPATEN SOLOK - Ager, Fani Septi; Mariya, Sri (JURNAL BUANA, 2024)
This study aims to determine how the influence of capital, length of business, working hours, and education on the income of traders around the Pesanggrahan Lake Singkarak Tourism Area, Solok Regency. This type of research is descriptive qualitative. The informants in this study were traders around the Pesanggrahan Lake Singkarak Tourism Area. The type of data used is primary data with interview data collection techniques. Data analysis is data collection, data presentation, data reduction and data verification. The results of this study indicate that: (1) Capital affects the income of traders at Pesanggrahan Lake Singkarak. This can be seen from the amount of capital spent by traders following the number or absence of tourists visiting. (2) Length of business does not affect the income of traders at Pesanggrahan Lake Singkarak. This can be seen from the length of business between each trader, although different, the income earned by traders is almost the same. (3) Working hours affect the income of traders at Pesanggrahan Lake Singkarak. This can be seen when there are events and holidays the working hours of traders will increase, meaning that the more income the traders will get. (4) Education does not affect the income of traders at Singkarak Lake Reservation. This can be seen from the education of each trader is different but the income earned by traders is almost the same.